2017
DOI: 10.1016/j.ejbas.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of chemical biocides and Acalypha wilkesiana leaf extract against postharvest fungal deteriogens of sweet orange (Citrus sinensis) fruits

Abstract: View related articles View Crossmark data Full Length Article Comparative effectiveness of chemical biocides and Acalypha wilkesiana leaf extract against postharvest fungal deteriogens of sweet orange (Citrus sinensis) fruits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Comparable activities were reported for other medicinal plants against other phytopathogens [15][16][17]. Findings from this study were also comparable to the effect of chemical fungicides reported earlier [18,19]. Our findings, thus, suggest that water soluble fractions of petroleum hydrocarbon possess constituents that can also prevent the mycelial growth and development of the test fungal pathogen.…”
Section: Resultssupporting
confidence: 88%
“…Comparable activities were reported for other medicinal plants against other phytopathogens [15][16][17]. Findings from this study were also comparable to the effect of chemical fungicides reported earlier [18,19]. Our findings, thus, suggest that water soluble fractions of petroleum hydrocarbon possess constituents that can also prevent the mycelial growth and development of the test fungal pathogen.…”
Section: Resultssupporting
confidence: 88%
“…Variability of the fungal communities in composition and structure in the samples from the three trees and across the four locations (Table 4) could be attributed to the fungal spore size and the degree of mycelial fragmentation; and subsequent aerosolisation (Adhikari et al, 2009;Gralton et al, 2011;Barberán et al, 2015;Spilak et al, 2015). Most of the isolated fungal species are important causative agents of postharvest diseases of cocoa, kola-nuts and citrus trees (Peever et al, 2005;Ezeibekwe et al, 2008;Singh et al, 2012;Anitha et al, 2014;Akinde et al, 2017). These key findings are noteworthy for improvement in sanitation and overall management of old plantations.…”
Section: Discussionmentioning
confidence: 99%
“…They were randomly picked using a mounting needle, and sub-cultured onto fresh PDA plates, and incubated for 5 days. All axenic strains were stored on PDA slants for further characterisation (Akinde et al, 2017).…”
Section: Enumeration Of Fungimentioning
confidence: 99%